2022
DOI: 10.1186/s12936-022-04373-6
|View full text |Cite
|
Sign up to set email alerts
|

Multi-country review of ITN routine distribution data: are ANC and EPI channels achieving their potential?

Abstract: Background Routine continuous distribution (CD) of insecticide-treated nets (ITNs) has been an important part of an overall ITN strategy to complement mass campaigns since the early 2000s. The backbone of CD implementation for many sub-Saharan African countries is distribution through antenatal care (ANC) and Expanded Programme for Immunizations (EPI) channels. Performance of these channels is often not monitored closely at the national level, nor is it reviewed globally, unlike the oversight p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Despite the usefulness of ITNs as key malaria control tools in SSA, there is reported low usage of ITNs in the region despite relatively high ownership, with barriers such as lack of awareness, poor usage knowledge, inadequate resources, and socio-cultural beliefs hindering the effectiveness of ITN interventions (Orish et al, 2021). Additionally, several factors have been identi ed as barriers or facilitators of ITN ownership and use at the individual and community levels (Miller et al, 2022;Scott et al, 2021;Orish et al, 2021). These include perceptions of malaria and ITNs, availability and affordability of ITNs, and environmental and climatic conditions (Miller et al, 2022;Orish et al, 2021;Scott et al, 2021) Among the factors identi ed, household characteristics may play a signi cant role in in uencing ITN utilisation, especially among children under-ve who are more vulnerable to malaria and depend on their caregivers for protection (Scott et al, 2021;Odufuwa et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the usefulness of ITNs as key malaria control tools in SSA, there is reported low usage of ITNs in the region despite relatively high ownership, with barriers such as lack of awareness, poor usage knowledge, inadequate resources, and socio-cultural beliefs hindering the effectiveness of ITN interventions (Orish et al, 2021). Additionally, several factors have been identi ed as barriers or facilitators of ITN ownership and use at the individual and community levels (Miller et al, 2022;Scott et al, 2021;Orish et al, 2021). These include perceptions of malaria and ITNs, availability and affordability of ITNs, and environmental and climatic conditions (Miller et al, 2022;Orish et al, 2021;Scott et al, 2021) Among the factors identi ed, household characteristics may play a signi cant role in in uencing ITN utilisation, especially among children under-ve who are more vulnerable to malaria and depend on their caregivers for protection (Scott et al, 2021;Odufuwa et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, several factors have been identi ed as barriers or facilitators of ITN ownership and use at the individual and community levels (Miller et al, 2022;Scott et al, 2021;Orish et al, 2021). These include perceptions of malaria and ITNs, availability and affordability of ITNs, and environmental and climatic conditions (Miller et al, 2022;Orish et al, 2021;Scott et al, 2021) Among the factors identi ed, household characteristics may play a signi cant role in in uencing ITN utilisation, especially among children under-ve who are more vulnerable to malaria and depend on their caregivers for protection (Scott et al, 2021;Odufuwa et al, 2020). However, there is limited evidence on how speci c household characteristics, such as household size, number of sleeping rooms, and the demographic characteristics of household heads, affect ITN utilisation among under-ve children in SSA (Seyoum et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Even at the global level, there is little public information. For example, a recent multi-country analysis found that the national ITN issuing rates at ANC across seven sub-Saharan countries and EPI for six sub-Saharan countries were 65% and 69%, respectively [ 14 ]. To help fill this knowledge gap, a historical analysis of bed net issuing rates through ANCs and CWCs across six years (2016–2021) was conducted.…”
Section: Introductionmentioning
confidence: 99%